Efficacy and Safety of Low-Intensity Shockwave Therapy for Vasculogenic Erectile Dysfunction - Mohamed Elzwawi; Salem Swieb; Moneer Badish (AlQalam Journal of Medical and Applied Sciences, 2026)
Vasculogenic erectile dysfunction (ED) is highly prevalent and frequently refractory to first-line therapies such as phosphodiesterase type 5 inhibitors (PDE5-Is). Low-intensity shockwave therapy (Li-SWT) has emerged as a regenerative modality that promotes angiogenesis and endothelial repair, offering potential long-term benefits. This study evaluated the efficacy and safety of Li-SWT in patients with vasculogenic ED unresponsive or partially responsive to PDE5-Is, and explored predictors of treatment response. In this prospective, open-label, single-arm trial, patients diagnosed with vasculogenic erectile dysfunction (ED) were enrolled between 2023 and 2024. Participants underwent 4 to 6 weekly sessions of low-intensity shockwave therapy (Li-SWT) using the Piezowave2 device, which delivered 4,000 shocks per session, complemented by a daily dosage of tadalafil at 5 mg. Efficacy was evaluated using the International Index of Erectile Function-5 (IIEF-5) and the Erection Hardness Score (EHS) at baseline and following the treatment. Twenty patients participated in this study, with a mean age of 55.9 years (±13.5). The mean baseline scores for the IIEF-5 and EHS were 10.9 (±4.5) and 2.1 (±0.8), respectively. Post-treatment, the IIEF-5 increased to 14.9 (±6.1), representing a mean difference of +3.95 (95% CI 1.56–6.34, p=0.002), and the EHS rose to 2.65 (±1.31), with a mean difference of +0.60 (95% CI 0.10–1.10, p=0.022). Six patients (30%) achieved “no ED,” while 40% displayed no clinically meaningful response. Responders (40%) were significantly younger (46.6 vs. 61.8 years, p=0.005), exhibited higher baseline IIEF-5 scores (14.1 vs. 8.8, p=0.003), and had fewer instances of hypertension (12.5% vs. 58.3%, p=0.047). Additionally, age showed a negative correlation with treatment response (r = −0.624, p=0.003). Li-SWT shows promise as a safe and moderately effective treatment for vasculogenic erectile dysfunction, especially in younger patients with mild to moderate baseline severity. Despite encouraging results, the lack of a control group, concurrent PDE5-I use, and small sample size limit generalizability.